1992
DOI: 10.1111/j.1432-1033.1992.tb16564.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on synthetic pathway of xylose‐containing N‐linked oligosaccharides deduced from substrate specificities of the processing enzymes in sycamore cells (Acer pseudoplatanus L.)

Abstract: We measured the activities of a-I ,3-mannosyl-glycoprotein ~-l,2-N-acetylglucosaminyltransferase, a-1,6-mannosyl-glycoprotein p-1,2-N-acetylglucosaminyltransferase, ~-3,4-mannosyl-glycoprotein p-1,2-xylosyltransferase and glycoprotein 3-a-~-fucosyltransferase in the Golgi fraction of suspension-cultured cells of sycamore (Acer pseudoplatanus L.) using fluorescence-labelled oligosaccharides as acceptor substrates for these transferase reactions. The structures of the pyridylaminated oligosaccharides produced by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 42 publications
3
34
0
Order By: Relevance
“…The bean cotyledon xylosyltransferase acts on glycopeptide acceptors having a terminal Bl-Zlinked GlcNAc residue on the Manal-3-arm and it was suggested that xylose in vivo is introduced after the action of both DGlcNAc-T I and a-mannosidase I1 since GlcNAcMan,GlcNAc,Asn was a poor xylose acceptor [lo]. For sycamore cell DXyl-T similar results have been reported, and this DXyl-T also required acceptors having the structural element GlcNAcpl-2Manal-3Man/3-R [26]. The substrate specificities of both of these plant p2Xyl-Ts are similar to that of the snail connective tissue DXyl-T.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The bean cotyledon xylosyltransferase acts on glycopeptide acceptors having a terminal Bl-Zlinked GlcNAc residue on the Manal-3-arm and it was suggested that xylose in vivo is introduced after the action of both DGlcNAc-T I and a-mannosidase I1 since GlcNAcMan,GlcNAc,Asn was a poor xylose acceptor [lo]. For sycamore cell DXyl-T similar results have been reported, and this DXyl-T also required acceptors having the structural element GlcNAcpl-2Manal-3Man/3-R [26]. The substrate specificities of both of these plant p2Xyl-Ts are similar to that of the snail connective tissue DXyl-T.…”
Section: Discussionsupporting
confidence: 61%
“…This is the first report of an animal xylosyltransferase acting on N-linked oligosaccharide chains. N-glycans containing xylose are common in the plant kingdom and plant xylosyltransferases involved in the biosynthesis of these glycoproteins have been described for Phaseolus vulgaris cotyledons [lo] and sycamore cells of Acer pseudoplatanus [26]. The bean cotyledon xylosyltransferase acts on glycopeptide acceptors having a terminal Bl-Zlinked GlcNAc residue on the Manal-3-arm and it was suggested that xylose in vivo is introduced after the action of both DGlcNAc-T I and a-mannosidase I1 since GlcNAcMan,GlcNAc,Asn was a poor xylose acceptor [lo].…”
Section: Discussionmentioning
confidence: 99%
“…According to the present results that clearly indicate in which Golgi compartment most PI +2 xylose and a1 +3 fucose residues are added to plant complex glycans and considering what has already been published on N-glycosylation in rice (Hayashi et al, 1990), bean (Sturm et a/., 1987) and sycamore (Tezuka et al, 1992), we propose a model for plant N-linked glycan processing in the Golgi apparatus. After a trimming of three glucoses and possibly one mannose residue in the ER, the glycoprotein is transported through the cis and the medial cisternae of the Golgi apparatus where the glycan can progressively be further matured to a G I C N A~~M~~, ( G I C N A C )~ structure.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, AtXylT activity was strongly decreased in the absence of MnCl 2 , or after addition of EDTA in the assay. Therefore, AtXylT has properties similar to most other xylosyltransferases (Johnson and Chrispeels, 1987;Tezuka et al, 1992) or glycosyltransferases characterized to date, except for soybean XylT which does not appear to require divalent cations (Zeng et al, 1997).…”
Section: Substrate Specificity and Biochemical Characterization Of Atmentioning
confidence: 99%
“…In plants, substrate specificities have been analyzed for most glycosyltransferases responsible for N-glycan maturation (Johnson and Chrispeels, 1987;Tezuka et al, 1992) and a distribution of the most typical plant glycosyltransferases in the Golgi was proposed from an indirect approach based on immunolocalization of their products. For instance, using antibodies against the main glycoepitopes present in plant N-glycans we have shown that b1,2-xylose is added mainly in the medial Golgi cisternae, a1,3-fucosylation occurs mostly in the trans Golgi (Fitchette et al 1994), while the plant Lewis a antennae biosynthesis is a late Golgi event occurring in the trans Golgi and trans Golgi network (TGN) (Fitchette et al, 1999).…”
Section: Introductionmentioning
confidence: 99%